'Who Had to Die so I Could Go Camping?': Shifting non-Native Conceptions of Land and Environment through Engagement with Indigenous Thought and Action. Issue 3 (2nd September 2021) - Bacon, J. M.
ABSTRACT: Scholarship in the area of social movements points to the importance of inter-group collaboration and alliance building. In the case of Indigenous-led movements and the issue of solidarity with non-Indigenous movement participants, scholarship at the intersection of Native studies and social movements suggests that such alliances can be built and sustained but that unlearning colonial attitudes and behaviors is central to this process. Through in-depth interviews with non-Native solidarity participants, this article considers how engagement with Indigenous thought and action re-shapes particpants' conceptions of environment and place. Findings suggest that such involvement calls attention to histories of violence as well as ongoing practices of dispossession causing activists to grapple not only with their personal and family histories but also with their evolving relationship with environmentalism.